Nasal Bridge Intramuscular Hemangioma - Hamir Basah, Zulkifli (Case Rep Otolaryngol, 2015)
Intramuscular haemangioma (IMH) is a benign mesenchymal tumour. It appears as a deep, nontender mass within the soft tissue, particularly in the extremities. This tumour may not be obvious on clinical examination. Head and neck IMHs represent only 13.5% of the total IMHs. The most common site for a head and neck IMH is the masseter muscle, followed by trapezius, sternocleidomastoid, and very rarely temporalis muscle. We present a patient with left nasal bridge swelling which was excised and histologically confirmed as intramuscular hemangioma.